Three axes in one device [News Briefs]. - Jones, W.D.
To orient themselves properly, smartphones require not just GPS capability but also an electronic compass, an accelerometer, and increasingly, digital gyroscopes, which can sense changes in an object's axis of rotation. up until now, gyroscopes measured movement around the three axes with three sensors-one for pitch, one for yaw, and another for roll. But in February, Stmicroelectronics unveiled a 4- by 4- by 1-millimeter gyroscope whose single sensing structure tracks all three angular motions. the device draws only 6 milliamps; two years ago, each one of ST's single-axis devices drew 5 mA.